2017
DOI: 10.1007/s13304-017-0461-9
|View full text |Cite
|
Sign up to set email alerts
|

To evaluate the efficacy of an acellular Flowable matrix in comparison with a wet dressing for the treatment of patients with diabetic foot ulcers: a randomized clinical trial

Abstract: The authors aimed to evaluate the efficacy of an advanced wound matrix (Integra Flowable Wound Matrix, Integra LifeScience Corp, Plainsboro, NJ, USA) for treating wounds with irregular geometries versus a wet dressing in patients with diabetic foot ulcers. Sixty patients with diabetic foot ulcers (Grades 3 Wagner) were included in this randomized clinical trial. The study was conducted in the General Surgery Unit and Geriatric of the Second University of Naples, Italy, in the last 12 months. Forty-six cases of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…They also noted lower amputation and rehospitalization rates. 61 Hu et al compared split grafting with ADM with split grafting alone and found that, in the ADM group, recurrence rates were lower, and wound and scar appearance was better, but wound closure rates were similar in both groups. 62 DermACELL, an ADM that has undergone a unique decellularization process resulting in thorough DNA removal, was evaluated in two studies compared with conventional care and Graftjacket ADM.…”
Section: Acellular Bioproductsmentioning
confidence: 99%
“…They also noted lower amputation and rehospitalization rates. 61 Hu et al compared split grafting with ADM with split grafting alone and found that, in the ADM group, recurrence rates were lower, and wound and scar appearance was better, but wound closure rates were similar in both groups. 62 DermACELL, an ADM that has undergone a unique decellularization process resulting in thorough DNA removal, was evaluated in two studies compared with conventional care and Graftjacket ADM.…”
Section: Acellular Bioproductsmentioning
confidence: 99%
“…Two recent RCTs with topical Pirferidone (with potential anti‐inflammatory/antifibrotic properties) had methodological limitations; neither were blinded, results were analysed per protocol, and there was a high dropout rate in one, and an unexpectedly low healing rate in the control group in the other . Four RCTs of products designed to promote healing; Chitosan and Isosorbide dinitrate, hyaluronic acid, an acellular flowable matrix, and the proteolytic fraction from latex P1G10 provided little support for the use of these agents in clinical practice because of a small number of recruited patients, nonblinding, per protocol analysis, and/or high drop‐out rates. One RCT of a gap‐junctional protein (ACT1, a connexin43‐based gel) in patients with noninfected neuropathic ulcers showed a significantly greater reduction in mean percent ulcer area from baseline to 12 weeks but with a high rate of withdrawal of consent and protocol noncompliance …”
Section: Recommendationsmentioning
confidence: 99%
“…The advanced wound matrix was well tolerated and in patients (13.04%) with graft failure had no clinical and/or laboratory inflammatory signs was observed [35].…”
Section: Short Commentarymentioning
confidence: 95%